Mitochondria: Aging, Metabolic Syndrome and Cardiovascular Diseases. Formation of a New Paradigm - A. V. Panov (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Cardiovascular diseases are among the major causes of mortality among aged people in most developed countries. Oxidative stress, which causes mutations of mitochondrial DNA and mitochondrial dysfunctions, was considered as the main mechanism of heart failure and other pathologies of old age. However, in recent years the prior paradigm of mechanisms of aging, oxidative stress and antioxidative defense was questioned and in some aspects even turned out to be wrong. In this review, we discuss the new data that led to the need to reconsider paradigms. We show that although the mitochondrial free radical theory of aging remains valid, the radical responsible for the aging is the protonated form of the superoxide radical, namely perhydroxyl radical, which was largely ignored all previous years. Perhydroxyl radical initiates the isoprostane pathway of lipid peroxidation (IPLP) of polyunsaturated fatty acids, which are part of the phospholipid core of the mitochondrial inner membrane. IPLP was discovered 30 years ago by Roberts and Morrow at the Vanderbilt University, but the mechanism of its initiation remained unknown. The IPLP causes formation of the racemic mixture of hundreds of biologically active products, named isoprostanes, and highly toxic molecules, first of all isolevuglandins. We distinguish two types of damages caused by IPLP during aging. The first one is associated with oxidative damages to cardiolipin and phosphatidylethanolamine (PEA), which result in disruption of polyenzymatic complexes of the oxidative phosphorylation system. The second type of dysfunctions is caused by the direct actions of toxic products on the lysine-containing proteins and PEA. To this type of mitochondrial damages evidently belongs the oxidative damage of the mitochondrial DNA polymerase, which results in a 20-fold increase in mutations of mitochondrial mtDNA.